2019
DOI: 10.1149/2.0081905jss
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Liquids for Non–Prestonian Chemical Mechanical Polishing of Polysilicon Films

Abstract: Slurries which yield non-Prestonian polysilicon (poly-Si) removal rates (RRs) are desirable during the fabrication of semiconductor and microelectromechanical systems (MEMS) devices. Here, we show that aqueous solutions of 250 ppm poly(diallyldimethylammonium chloride) (PDADMAC), DADMAC (monomer of PDADMAC) or guanidine carbonate (GC) at pH 10 give high poly-Si polish rates. Addition of 25 ppm cetylpyridinium bromide (CPB), a cationic surfactant to any of these solutions modifies their polish performance to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Under low pressure conditions, there is basically no removal rate in the nonabrasive polishing liquid. 26 Compared with non-abrasive polishing liquid, a certain removal rate can be obtained under low pressure (1.5 psi).…”
Section: Resultsmentioning
confidence: 99%
“…Under low pressure conditions, there is basically no removal rate in the nonabrasive polishing liquid. 26 Compared with non-abrasive polishing liquid, a certain removal rate can be obtained under low pressure (1.5 psi).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, several studies have shown that the adsorption of the additive molecules present in CMP slurries on the film being polished can be influenced by resonance, polarizability, chain length, and inductive, dispersion and steric effects. 13,14,[21][22][23] For example, Patri et al 14 found that the copper film RRs obtained with glycine and β-Alanine as additives in silica slurries were significantly different from each other in the pH range 2-10 and argued that the carbon chain length controlled the reactivity of the additives. In another study on polishing of SiN films, Penta et al 13 showed that picolinic acid was more effective for nitride suppression than proline and suggested that the differences were due to steric effects.…”
Section: Resultsmentioning
confidence: 99%